Penilaian kualitas visual lanskap pada koridor jalan bypass Dharma Giri Kota Gianyar - I Putu Agus Heriyasa Putra; I Gusti Agung Ayu Rai Asmiwyati (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Bypass Dharma Giri Street is a commercial route with high mobility along the road corridor functioned as a trade and service area. This research showed that Bypass Dharma Giri Street does not have an optimal arrangement of landscape elements so there are several problems on the site. The problems that were found include: illegal parking, mismatch arrangement of planter box, street vendors selling in the sidewalk area as well as advertising boards and billboards that are installed carelessly. These have an impact on the visual comfort of users, therefore it is important to assess the visual quality of the landscape. This study aimed to assess the visual quality of the landscape of Bypass Dharma Giri Street. This research used a survey method with an analysis of landscape beauty estimation used Scenic Beauty Estimation (SBE) and analysis of impressions that arise in the landscape used Semantic Differential (SD). The result of the research was the score of the visual quality of the landscape of Bypass Dharma Giri Street. The assessment shows that the visual quality of the landscape of Bypass Dharma Giri Street is dominated by landscapes that have moderate visual landscape quality. Recommendations for the arrangement and maintenance of landscape elements based on high visual quality are needed, therefore they can be used as input to improve the visual quality of the landscape of the Bypass Dharma Giri Street corridor.